2021
DOI: 10.23960/mtk/v9i4.pp343-359
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-LKPD Matematika Berbasis Problem Solving Pokok Bahasan Pola Bilangan

Abstract: The type of this research is Research and Development. The research purpose was to develop and determine the feasibility of e-LKPD mathematics based on Problem Solving number pattern material for class VIII Junior High School. The development model used in this research is ADDIE. The subject in this research is all student of class VIII B and VIII C SMP Muhammadiyah Piyungan. The data obtained were analyzed using descriptive qualitative analysis and descriptive quantitative analysis. The results showed that e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As it was done by Amelia et al (2020), who concludes that digital worksheets can train students' metacognitive awareness through metacognitive activities. Similarly, Darmawan and Yuwaningsih (2021) conclude that digital worksheets can train and improve students' mathematical problem-solving abilities. This corresponds to the average score of student problem solving assignments of 7.62 (Table 6).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As it was done by Amelia et al (2020), who concludes that digital worksheets can train students' metacognitive awareness through metacognitive activities. Similarly, Darmawan and Yuwaningsih (2021) conclude that digital worksheets can train and improve students' mathematical problem-solving abilities. This corresponds to the average score of student problem solving assignments of 7.62 (Table 6).…”
Section: Discussionmentioning
confidence: 87%
“…The worksheet developed contains reinforcement materials, systematic activities based on learning approaches (Amelia et al, 2020;Pulungan et al, 2022;Sharma, 2022), and practice questions. The results showed that digital worksheets could develop critical and logical thinking skills (Huang et al, 2007;Puspita & Dewi, 2021), train mathematical problem-solving skills (Darmawan & Yuwaningsih, 2021), and literacy (Mulyasari et al, 2022). In addition, learning using digital worksheet also makes students happy and interested in mathematics (Pulungan et al, 2022), increasing cases of learning activity and independence (Amelia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The web-based E-LKPD for Indonesian History for Grade XI SMA aims to arouse students' curiosity and motivate students to study independently. E-LKPD is in the form of student work guides to make it easier for students to understand learning material in electronic (digital) form whose application uses desktop computers, notebooks, smartphones and cellphones, a set of basic activities that students must carry out to maximize understanding in an effort to achieve learning goals (Darmawan & Yuwaningsih, 2021;Farman et al, 2021;Ramadhana & Hadi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Teaching materials can be interpreted as components of message content in the curriculum that must be conveyed to students in the form of facts, concepts, principles or rules, procedures, problems, and so on (Octaviana et al, 2022;Purnama & Suparman, 2020;Wahyuni et al, 2021). The use of teaching materials in teaching and learning activities is adapted to the era of the industrial revolution 4.0, namely all human activities utilize existing information technology (Darmawan & Yuwaningsih, 2021;Farman et al, 2021;Ramadhana & Hadi, 2021). Good learning activities can help students understand the lesson (Ariyani & Ganing, 2021;Indrapangastuti, 2014;Khofifah & Ramadan, 2021).…”
Section: Introductionmentioning
confidence: 99%